Microstructural, mechanical and tribological characterization of Co–20 wt% WC composite elaborated by solid-phase sintering of Co–W–C powders mixture. (3rd July 2022) - Aouchiche, Lylia; Alhussein, Akram; Nechiche, Mustapha; Retraint, Delphine; Amirouche, Saifi; Azem, Said
ABSTRACT: In this paper, we present the synthesis of a Co–WC compound with 80% of cobalt in a single step by sintering powders compacted and previously milled for 10 h. The purpose of this work is to obtain a fine structure avoiding the formation of mixed carbides and reducing the WC/WC interfaces. The original powder mixture contained 80 wt% Co, 13 wt% W and 7 wt% C. The Co–20% WC metal matrix composite was successfully synthesized with a very fine and homogeneous structure. It presented a good wear resistance and showed that increasing the applied load from 5 to 10 N led to decrease the friction coefficient from 0.52 to 0.35 (sample speed = 10 cm/s) and from 0.90 to 0.61 (sample speed = 20 cm/s). The hardness and Young's modulus of Co phase and WC grains, measured by nanoindentation technique, were 0.78/79.9 and 5.78/164.6 GPa, respectively. GRAPHICAL ABSTRACT: UF0001